Heatstroke: a multicenter study in Southwestern China - Shi, Lvyuan; Wang, Bo; Wu, Qin; Yang, Jing; Wang, Lietao; Wan, Dingyuan; Wang, Yucong; Feng, Zhongxue; Zhang, Wei; Li, Li; Wang, Wenhu; Chen, Jun; et al. (Frontiers in Public Health, 2024)
Background An increase in Heatstroke cases occurred in southwest China in 2022 due to factors like global warming, abnormal temperature rise, insufficient power supply, and other contributing factors. This resulted in a notable rise in Heatstroke patients experiencing varying degrees of organ dysfunction. This descriptive study aims to analyze the epidemiology and clinical outcomes of Heatstroke patients in the ICU, providing support for standardized diagnosis and treatment, ultimately enhancing the prognosis of Heatstroke. Methods A retrospective, multicenter, descriptive analysis was conducted on Heatstroke patients admitted to ICUs across 83 hospitals in southwest China. Electronic medical records were utilized for data collection, encompassing various aspects such as epidemiological factors, onset symptoms, complications, laboratory data, concurrent infections, treatments, and patient outcomes. Results The dataset primarily comprised classic heatstroke, with 477 males (55% of total). The patient population had a median age of 72 years (range: 63–80 years). The most common initial symptoms were fever, mental or behavioral abnormalities, and fainting. ICU treatment involved respiratory support, antibiotics, sedatives, and other interventions. Among the 700 ICU admissions, 213 patients had no infection, while 487 were diagnosed with infection, predominantly lower respiratory tract infection. Patients presenting with neurological symptoms initially (n = 715) exhibited higher ICU mortality risk compared to those without neurological symptoms (n = 104), with an odds ratio of 2.382 (95% CI 1.665, 4.870) (p = 0.017). Conclusion In 2022, the majority of Heatstroke patients in southwest China experienced classical Heatstroke, with many acquiring infections upon admission to the ICU. Moreover, Heatstroke can result in diverse complications.